1993
DOI: 10.1021/j100144a031
|View full text |Cite
|
Sign up to set email alerts
|

Proton transfer between water molecules: a theoretical study of solvent effects using the continuum and the discrete-continuum models

Abstract: Proton transfer between two water molecules both in the gas phase and in solution has been studied at the HF/6-311G** level. For the gas phase we have characterized the reduced potential energy surface. Proton transfer in solution has been modeled with a pure continuum model and with a mixed discretecontinuum model where the two water molecules between which the proton is transferred are surrounded with four more water molecules and a continuum. Both in the gas phase and in solution the proton transfer between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 4 publications
3
30
1
Order By: Relevance
“…This result is in agreement with other experiments on glycine tautomerization kinetics 26, 27. All calculations23, 28–30 except some molecular dynamics simulations31, 32 yielded a free energy barrier for the direct proton transfer mechanism much lower than the experimental one 25. Tuñón et al suggested that the neutral conformer, which is the precursor of the zwitterion, has a very short lifetime, and the experimentally measured free energy of activation is associated with the conformational rearrangement of the neutral isomer 33.…”
Section: Introductionsupporting
confidence: 89%
“…This result is in agreement with other experiments on glycine tautomerization kinetics 26, 27. All calculations23, 28–30 except some molecular dynamics simulations31, 32 yielded a free energy barrier for the direct proton transfer mechanism much lower than the experimental one 25. Tuñón et al suggested that the neutral conformer, which is the precursor of the zwitterion, has a very short lifetime, and the experimentally measured free energy of activation is associated with the conformational rearrangement of the neutral isomer 33.…”
Section: Introductionsupporting
confidence: 89%
“…MP2 also performs well in comparison to CCSD(T); the corresponding proton affinity at the CCSD(T)/aug-cc-pVDZ level is -170.2 kcal/mol, only 1.4 kcal/mol away from the CBS limit of -171.6 kcal/mol. contrary to previous calculations (Tortonda et al 1993) at the HF level of theory which have found a surface with a double minimum.…”
Section: Molecular Science 139contrasting
confidence: 97%
“…The calculated rocking COO À vibrational mode of the Gly molecule was coupled with C-N deformational mode, which was obtained at 503 and 510 cm À1 in nRs and SERS respectively. The coupled COO À rocking vibrational mode was observed at 508 and 505 cm À1 in nRs and SERS respectively [15,42].…”
Section: Coo à Vibrationsmentioning
confidence: 99%
“…Normally, the CH 2 scissoring vibrational modes fall in the region 1450e1390 cm À1 [40]. In Gly molecule, the calculated CH 2 scissoring in plane bending vibrational mode was coupled with COO À asymmetrical stretching vibrational mode, which was predicted at 1454 and 1450 cm À1 in nRs and SERS respectively, and the corresponding vibrational modes were observed at 1444 and 1442 cm À1 in nRs and SERS [42]. The calculated coupled CH 2 scissoring in plane bending vibrational mode and COO À symmetrical stretching vibrational mode was obtained at 1420 and 1399 cm À1 in nRs and SERS respectively.…”
Section: Ch 2 Vibrationsmentioning
confidence: 99%